Üriner sistem enfeksiyonları tanısında ve rekürrens riskini öngörmede A vitamini ve diğer biyobelirteçlerin rolleri - Seçilmiş, Nurullah (Fırat Üniveristesi, 2026)
ÖZET Üriner sistem enfeksiyonları (ÜSE), böbrek, üreter, mesane, üretrayı kapsayabilen ve her yaşta ve cinsiyette gerçekleşebilen mikrobiyal enfeksiyonları kapsayan bir terimdir. Rekürren ÜSE, komplike olsun veya olmasın bir yılda en az 3 enfeksiyon veya son 6 ayda en az 2 enfeksiyon olarak tanımlanmaktadır. Bu çalışmada, rekürren üriner sistem enfeksiyonu hastalarında serum SIRT1, NF-kB, HSP27, IMA ve Vitamin A düzeylerinin normal popülasyondan farkını ve bu parametrelerin düzeylerinin üst ve alt üriner sistem enfeksiyonlarındaki farklılıklarını araştırmak amaçlanmıştır. Çalışma grubu 50 adet herhangi bir nedenle sağlık kontrolü yapıp çalışmayı kabul eden sağlıklı bireyler, 75 adet rekürren sistit ve 75 adet rekürren pyelonefrit tanısı almış hastalardan oluşmaktadır. Serum SIRT-1, NF-kB, HSP27, IMA düzeyleri ELISA yöntemiyle, plazma Vitamin A düzeyleri ise HPLC yöntemi ile ölçülmüştür. Kontrol grubunda HSP27 düzeyleri hasta gruplarına göre yüksek bulunurken bu yükseklik sadece pyelonefrit grubu ile karşılaştırıldığında istatistiksel olarak anlamlı bulunmuştur (p=0,046). NF-kB seviyeleri pyelonefrit grubunda sistit ve kontrol gruplarına göre anlamlı yüksek bulunmuştur (sistit grubu için p=0,046; kontrol grubu için p=0,002). Kontrol grubu SIRT1 düzeyleri sistit ve pyelonefrit grubuna göre istatistiksel anlamlı olarak yüksek bulunmuştur (sistit grubu için p= 0,041; pyelonefrit grubu için p< 0,001). Kontrol grubu IMA düzeyleri sistit ve pyelonefrit grubuna göre anlamlı düşük bulunmuştur (sistit grubu için p= 0,029; pyelonefrit grubu için p=0,037). Vitamin A düzeyleri ise pyelonefrit grubunda kontrol ve sistit gruplarına göre anlamlı düşük bulunmuştur (sistit grubu için p=0,011; kontrol grubu için p=0,002). SIRT1 ve NF-kB parametreleri arasındaki negatif ilişkinin rekürren ÜSE'lerin oluşumunda rol alabileceği, IMA'nın bu hastalardaki oksidatif stres yükünü yansıtabileceği, HSP27 ve Vitamin A'nın rekürren ÜSE'lere karşı koruyucu görevleri olabileceği sonucuna varılmıştır. Anahtar Kelimeler: Rekürren ÜSE, Vitamin A, IMA, SIRT1, NF-kB

ABSTRACT THE ROLES OF VITAMIN A AND OTHER BIOMARKERS IN THE DIAGNOSIS OF URINARY TRACT INFECTIONS AND IN PREDICTING RECURRENCE RISK Urinary tract infections (UTIs) are a term encompassing microbial infections that can affect the kidneys, ureters, bladder, and urethra, and can occur at any age and in both sexes. Recurrent UTI is defined as at least 3 infections in one year, or at least 2 infections in the last 6 months, whether complicated or not. This study aimed to investigate the differences in serum SIRT1, NF-kB, HSP27, IMA, and Vitamin A levels in patients with recurrent urinary tract infections compared to the normal population, and to examine the differences in the levels of these parameters in upper and lower urinary tract infections. The study group consisted of 50 healthy individuals who had undergone a health check for any reason and agreed to participate in the study, and 75 patients diagnosed with recurrent cystitis and 75 patients diagnosed with recurrent pyelonephritis. Serum SIRT-1, NF-kB, HSP27, and IMA levels were measured using ELISA, while plasma Vitamin A levels were measured using HPLC. HSP27 levels were found to be higher in the control group compared to the patient groups, and this elevation was statistically significant only compared to the pyelonephritis group (p=0.046). NF-kB levels were found to be significantly higher in the pyelonephritis group compared to the cystitis and control groups (p=0.046 for the cystitis group; p=0.002 for the control group). SIRT1 levels in the control group were found to be statistically significantly higher than in the cystitis and pyelonephritis groups (p=0.041 for the cystitis group; p<0.001 for the pyelonephritis group). IMA levels in the control group were found to be significantly lower than in the cystitis and pyelonephritis groups (p=0.029 for the cystitis group; p=0.037 for the pyelonephritis group). Vitamin A levels were also found to be significantly lower in the pyelonephritis group compared to the control and cystitis groups (p=0.011 for the cystitis group; p=0.002 for the control group). It was concluded that the negative relationship between SIRT1 and NF-kB parameters may play a role in the development of recurrent UTIs, that IMA may reflect the oxidative stress burden in these patients, and that HSP27 and Vitamin A may have protective functions against recurrent UTIs. Keywords: Recurrent UTI, Vitamin A, IMA, SIRT1, NF-kB
The roles of vitamin A and other biomarkers in the diagnosis of urinary tract infections and in predicting recurrence risk
Keywords: Biyokimya